The pattern of TSH and fT4 levels across different BMI ranges in a large cohort of euthyroid patients with obesity - Mele, Chiara; Mai, Stefania; Cena, Tiziana; Pagano, Loredana; Scacchi, Massimo; Biondi, Bernadette; Aimaretti, Gianluca; Marzullo, Paolo (Frontiers in Endocrinology, 2022)
Purpose: A multifold association relates the hypothalamo-pituitary-thyroid axis to body weight. The potential underlying mechanisms are incompletely understood. Further, the mild severity of obesity and the small proportion of individuals with obesity in so far published cohort studies provide little insights on metabolic correlates of thyroid function in obesity. Methods: We retrospectively enrolled 5009 adults with obesity (F/M, 3448/1561; age range, 18-87 years; BMI range, 30.0-82.7 kg/m2), without known thyroid disease in a study on TSH and fT4 levels, lipid profile, glucose homeostasis and insulin resistance, anthropometric parameters including BIA-derived fat mass (%FM) and fat-free mass (FFM). Results: The overall reference interval for TSH in our obese cohort was 0.58-5.07 mIU/L. As subgroups, females and non-smokers showed higher TSH levels as compared to their counterparts (p<0.0001 for both), while fT4 values were comparable between groups. There was a significant upward trend for TSH levels across incremental BMI classes in females, while the opposite trend was seen for fT4 levels in males (p<0.0001 for both). Expectedly, TSH was associated with %FM and FFM (p<0,0001 for both). TSH and fT4 showed correlations with several metabolic variables, and both declined with aging (TSH, p<0.0001; fT4, p<0.01). In a subgroup undergoing leptin measurement, leptin levels were positively associated with TSH levels (p<0.01). At the multivariable regression analysis, in the group as a whole, smoking habit emerged as the main independent predictor of TSH (β=-0.24, p<0.0001) and fT4 (β=-0.25, p<0.0001) levels. In non-smokers, %FM (β=0.08, p<0.0001) and age (β=-0.05, p<0.001) were the main significant predictors of TSH levels. In the subset of nonsmokers having leptin measured, leptin emerged as the strongest predictor of TSH levels (β=0.17, p<0.01). Conclusions: Our study provides evidence of a gender- and smoking-dependent regulation of TSH levels in obesity.